Reducing the use of seclusion in a secure service for women. (28th October 2014) - Long, Clive G; West, Rachel; Afford, Matthew; Collins, Lesley; Dolley, Olga
Abstract: Reducing the use of seclusion to deal with challenging behaviour is a priority in secure services for women. This study describes the concurrent introduction of a series of initiatives based on recovery principles and the full involvement of patients in their risk management plans. Following change implementation, the first 19 patients who had completed one year of treatment were matched with 19 patients who had completed their first year of treatment before change. A significant decline in both the number of seclusions and risk behaviour post-change was complemented by improved staff ratings of institutional behaviour, increased treatment engagement and a reduction in time spent in medium security. Staff and patients differed in terms of their ratings of the most effective strategies introduced. Patients favoured the Relational Security item of increased individual engagement and timetabled Behaviour Chain Analysis sessions. Staff viewed on ward training and use of de-escalation techniques as most effective. Findings confirm results from mixed gender forensic mental health samples that seclusion can be successfully reduced without an increase in patient violence or alternative coercive strategies. Limitations of the study are discussed along with the need for future evaluations to address issues of fidelity and utilise vigorously designed case studies.